The Neolithic Demographic Transition and its Consequences - Bocquet-Appel, Jean-Pierre (Springer, 2017)
The signal of a relatively abrupt increase, in the immature proportion of skeleton is observed in cemeteries during the foraging-farming transition. This signal is interpreted as the signature of a major demographic shift in human history,now known as the Neolithic Demographic Transition (NDT).